Peri-interventional ischemic stroke after coronary angiography: a large-scale nationwide cohort analysis from 2006 to 2020. (3rd October 2022) - Bay, B; Gossling, A; Remmel, M; Koester, L; Blaum, C M; Becher, P M; Zengin-Sahm, E; Rimmele, D L; Clemmensen, P; Seiffert, M; Blankenberg, S; Brunner, F J; et al.
Abstract: Background: Ischemic stroke after coronary angiography is a life-threatening complication, leading to high mortality and long-term sequelae in surviving patients. Contemporary data from a European nationwide perspective are however lacking. Purpose: We aimed to investigate the incidence, temporal trends, and outcome of ischemic stroke complicating coronary angiography in a German nationwide cohort. Methods: A retrospective analysis of healthcare records from 2006–2020 based on ICD-10 and OPS codes obtained from the German Federal Statistical Office was carried out. Patients ≥18 years of age hospitalized for coronary angiography (both diagnostic and percutaneous interventions) were included in this analysis. Ischemic stroke events as well as co-morbidities were identified using ICD-10 and OPS codes. The outcome of interest was in-hospital mortality. Multivariable logistic regressions were computed for the association of ischemic stroke with in-hospital mortality adjusting for age, gender, hypertension, hyperlipoproteinemia, and diabetes mellitus. Results: Overall 5, 098, 751 cases of patients undergoing coronary angiography (mean age 68.7±11.4 years; 28.0% female) between 2006 and 2020 were included. Ischemic stroke occurred in 3, 808 (0.07%) patients. In comparison, individuals who suffered from peri-interventional ischemic stroke were older (70.8±11.1 vs. 68.7±11.4; p<0.001), more likely female (33.4% vs. 27.9%; p<0.001), and differed significantly according to their clinical characteristics (see Table 1). Patients with ischemic stroke had a significantly longer in-hospital stay (18.3±15.5 vs. 6.4±8.0 days; p<0.001), and higher rates of in-hospital mortality (18.0% vs. 3.2%; p<0.001) compared to patients without ischemic stroke. After multivariable adjustment, ischemic stroke remained independently associated with a higher risk of in-hospital mortality with an Odds ratio of 6.5 (95% Confidence Interval: 5.9, 7.1; p<0.001). Also, incidence of peri-interventional stroke increased gradually from 0.03% in 2006 to 0.12% in 2020 (see Figure 1). Conclusion: In a contemporary nationwide cohort of patients hospitalized for coronary angiography spanning 15 years, the incidence of ischemic stroke remained low, although a gradual increase from 2006 to 2020 was documented. The occurrence of ischemic stroke was independently associated with a markedly increased risk of in-hospital mortality. These findings might be helpful in evaluating patients undergoing coronary angiography and to reduce the high mortality and morbidity associated with this complication in future. Funding Acknowledgement: Type of funding sources: None.